Ventajas e inconvenientes del cooperativismo agrario para el desarrollo regional aragonés - Rubio Gracia, José Luis (Geographicalia, 2017)
The agricultural co-operative system was born in Aragon, as in many other regions, with un ideological load that still is latent. This load brought it to be considered as a solution to rural problems, raising some incorrect outlines. The aim of this study is to analyse the advantages and, above all, the limitations and disadvantages of the co-operative system at the present time. Its efficacy before the current productivity requirements and the viability of these exploitations are valued with rational criteria.